An observational study of Senior Citizen at Senior Citizen Home of Tanahun District of Nepal - Sapkota, Poonam Pokhrel (Journal of Balkumari College, 2019)
Background: All countries have to face the population aging sooner depending on their degree of development; however, elderly care is predicted to soon become a major concern for developing countries such as Nepal. Methodology: A qualitative study was conducted in a senior citizen home of Tanahun district. General health check up of the 30 elderly followed by 2 focus group discussion and one Kll with provider was done to know the status of elderly and their perception towards senior citizen home. Results: Majority of the elderly were abandoned by their family members due to financial sufferings, and some of them left their home in search of their own comfort zone. Majority of them got old aged allowance which is the only way of financial security. They were living happily in the home though they missed their family in some occasion because they could have spent their leisure time by sharing their emotions and feelings with same age groups. Conclusions: Concept of senior citizen home has to be broaden up from the living home of poor old people to relaxing comfort home for elderly. Good management and facility should be incorporated with multi disciplinary team to take care of elderly to spend dignified life in senior citizen home as well.